Prevalence and associated factors of dyslipidemia among university students in Central Thailand: a cross-sectional study - Pootong, Anek; Kittiteerasack, Priyoth; Pattarapanitchai, Parichart; Choomean, Sirinart (Journal of Associated Medical Sciences, 2023)
Background: Dyslipidemia is regarded as a significant risk factor for atherosclerotic cardiovascular diseases (ASCVDs). Currently, there is limited data regarding dyslipidemia among Thai university students. Objective: This study aimed to examine the prevalence of dyslipidemia and its related factors among university students in the central region of Thailand. Materials and methods: In this cross-sectional study, a total of 434 students aged 18-25 years at Thammasat University and Kasetsart University were recruited using simple random sampling. Fasting venous blood samples were obtained, and plasma lipid profiles were assessed by an automated analyzer. Dyslipidemia was formally characterized according to the National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP III) guidelines. Demographic information, dietary behavior, and physical activity were collected using questionnaires. Anthropometric measures were also performed according to a standard protocol. Results: The prevalence of elevated total cholesterol, high-risk HDL-C, elevated LDL-C, and elevated triglycerides was 30.4, 18.2, 20.0, and 11.8%, respectively. The most common adverse lipid parameter was total cholesterol in both genders. Obesity and high fat intake were significantly associated with dyslipidemia (p<0.05). Conclusion: This research revealed a significant occurrence of dyslipidemia, primarily driven by elevated total cholesterol, among university students in Thailand. Obesity and high fat intake are significant risk contributors to dyslipidemia. These findings emphasize the need for awareness, prevention, and management strategies targeting this population.